INVESTMENT DECISION , CAPITAL DECISION , INDUSTRY PERFORMANCE , ECONIMIC MACROS AS ANTECEDENT VARIABLES OF FINANCIAL RISK MANAGEMENT AND FINANCIAL DISTRESS AGAINST VALUE OF THE FIRM WITH GCG AS A VARIABLE MODERATING FOR MANUFACTURING COMPANIES REGISTERED ON THE INDONESIAN STOCK EXCHANGE - Pristiana, Ulfi (Archives of Business Research, 2018)
The purpose of this study is to analyze and prove the effect of Investment Decision, Capital Decision, Industry Performance, Macro Economic As Antecedent Variables of Financial Risk Management And Financial Distress To Value Of The Firm With GCG As Moderating Variables. The population of this study is manufacturing companies listed on the BEI from 2014 to 2016 . Using the method of purposive sampling it was found 40 manufacturing companies as research samples. The result of this research shows that Investment Decision, Capital Decision , Industry Performance , Macro Economic, Financial Distress and GCG have significant influence to the company value of the firm , but Financial Risk Management has no significant influence to company value of the firm . GCG moderates significantly the influence of Financial Distress and Financial Risk Management on Value of the firm